Diversifikasi Olahan Susu Sapi Segar Menjadi Produk Kefir untuk Minuman Probiotik dan Masker Wajah di Kelurahan Plalangan Gunungpati Semarang - Haniif Prasetiawan; Bayu Triwibowo; Ratna Dewi Kusumaningtyas; Zuhriyan Ash Shiddieqy Bahlawan; Catur Rini Widyastuti (Universitas Teuku Umar, 2022)
Plalangan Village is one of the villages that produce fresh cow's milk in the administrative area of Gunungpati District, Semarang City, Central Java Province. The average daily activity of residents of Terwidi Village RT02 RW04, Plalangan Village, Gunungpati District, Semarang City in particular is raising cattle. The number of cattle breeders is 40 people who are members of the Ngudi Rahayu Terwidi Dairy Cattle Group (KTSP). The current number of cows is 75 heads, much lower than 5 years ago. The decline in the number of cows is due to the fact that they think that a dairy business that only relies on dairy products does not provide a steady income. Even though there is a lot of potential that can be developed from the dairy cattle business, including the diversification of dairy products. Kefir is a heterofermentative fermented product that has a taste, color and texture that resembles yogurt and has a distinctive aroma like tape. Kefir products circulating in the community today are not only consumed as probiotic drinks but can also be used as cosmetic products, such as masks. The main program will be carried out by the Community Service (PKM) team by empowering dairy cattle businesses through diversification of fresh cow's milk products to become high-value products, namely kefir which can be used as probiotic drinks and face masks.